Innovation Strategy in Increasing Village Economic Capacity Through BUMDes - Wulandari, Triyana; Puspitasari, Riska; Kadarsih, Sri; Husairi, Ridwan; Setiawan, Andi; gusti, Gusti (CV. Zabags Qu Publish, 2023)
This research is about BUMDes. BUMDes is a form of implementation of the Village Law, which makes villages the spearhead of development. Utilizing village potential provides benefits and interests for the community to achieve the welfare of local residents. The initial potential is the development of BUMDes (Village-Owned Enterprises) which serve as a driver of the village economy. However, as time goes by, quite a few villages experience failure in running their businesses, this is due to the lack of human resource capacity in managing BUMDes. This Community Service (Abdimas) activity aims to find out BUMDes innovation strategies in utilizing regional economic potential with various types of potential as a form of improving the village economy and being able to contribute to the village's original income. The method used is the community empowerment method using the technique of providing knowledge through lectures, then discussions with Focus Group Discussions (FGD) to find the problems faced by the village. The results obtained from this activity are increased understanding of village finances and the strengths and weaknesses of BUMDes Sidomukti, Dendang District. So that BUMDes can be managed better in the future.